Phosphate supplementation in exercise and sport - Kreider, R. B. (Macroelements, Water, and Electrolytes in Sports Nutrition, 1999)
Analysis of well-controlled contemporary research tends to support the hypothesis that short-term supplementation of phosphate (particularly sodium phosphate) may alter various physiological parameters which may affect endurance exercise performance. In this regard, in a variety of conditions and subject populations, phosphate loading has been reported to 1.) elevate extracellular and intracellular phosphate concentrations romoting a phosphate-stimulated glycolysis; 2.) attenuate anaerobic threshold 3.) increase the availability of phosphate for oxidative phosphorylation and creatine phosphate synthesis; 4.) promote 2,3-DPG synthesis; 5.) affect myocardial and cardiovascular responses to exercise; 6.) increase peripheral extraction of oxygen; 7.) increase maximal oxygen uptake; and, 8.) improve endurance exercise performance and/or efficiency. Although these findings are promising, it should be noted that not all studies report ergogenic benefit of phosphate loading possibly due to differences in the type and amount of phosphate ingested, the experimental design and procedures employed, and the type of exercise evaluated. Moreover, the specific mechanisms of action remain to be fully understood. Additional research is necessary to evaluate the effects of phosphate loading in various asymptomatic and symptomatic populations under varying exercise conditions. In addition, research should investigate the ergogenic value of phosphate loading for athletes engaged in a variety of athletic events.